Quality of life, fatigue and markers in sarcoidosis: A section from Turkey - Bardakci, Mustafa Ilteris; Ayhan Albayrak, Gulhan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Sarcoidosis can affect every organ with varying frequency based on ethnicity, gender and age. We aimed to evaluate the health-related quality of life (HRQoL) and fatigue levels of our sarcoidosis patients. However, our second aim is to determine whether patient or disease markers correlate with quality of life assessment questionnaires.Materials and Methods: Pulmonary sarcoidosis patients who were followed up in the chest diseases outpatient clinic of our hospital were included in this prospective study. In the follow-up of 2023, routine blood tests, angiotensin-converting enzyme (ACE), posteroanterior lung (thorax computed tomography in patients with parenchymal involvement) were requested from the patients. Participants were asked to fill out the short-form 36-item questionnaire (SF-36), fatigue assessment scale (FAS) and fatigue severity scale (FSS) under the control of the outpatient clinic.Results: A total of 189 patients, 139 (73.5%) female and 50 (26.5%) male, diagnosed with Sarcoidosis were included. The mean age of our patients was 53.1±13.6. ACE (IU/L) 68.5±44.5. Of the patients we followed up for pulmonary sarcoidosis, 111 (58.7%) had single organ involvement and 78 (41.3%) had additional organ involvement. FAS; It was high in 103 (64.3%) patients and 29 (15.3%) were very tired. FSS value was 4.45±0.7 (3-5.88). All SF-36 parameters were lower than expected; MH and SF was minimally lower, PF, RP, BP, GH, RE and VT were significantly lower. SF-36 scores were found to be lower in the women and additional organ involvement participating.Conclusion: We found a significant decrease in HRQoL and an increase in fatigue scores of our patients. These changes were more pronounced in women participating in the study than in men. In addition, the involvement of additional organs with the lung negatively affected the quality of life.